Secure Communication Scheme Based on Synchronization of Non-Identical Hyperchaotic Systems - Olusola, O.I.; Oyeleke, K.S.; Vincent, U.E.; Njah, A. N. (Journal of Applied Nonlinear Dynamics, 2026)
In this work, a secure communication scheme based on the synchronization of non-identical hyperchaotic systems is considered. Using hyperchaotic Lorenz and L ü as prototype oscillators, a secure communication scheme based on synchronization of different hyperchaotic systems with unknown parameters is presented. The communication scheme consists of a transmitter, which comprises the hyperchaotic carrier and modulator, and a receiver, which comprises the hyperchaotic response and a demodulator. Appropriate controllers and parameter update laws are designed to achieve synchronization between the hyperchaotic drive and hyperchaotic response systems and achieve the estimate of unknown parameters simultaneously. The message signal is recovered by the identified parameter and the corresponding demodulation method. Numerical simulations were performed to show the validity and feasibility of the designed secure communication scheme.